Dynamic of blood glucose levels in the model of experimental diabetic retinopathy and different ways to correct it - Y. Sirman; I. Savytskyi; O. Blavatska (Kazimierz Wielki University, 2021)
The aim of our study was to analyze the changes in the blood glucose level in experimental animals that simulated diabetic retinopathy and against the background of its correction. The obtained results show the development of experimental diabetes when streptozotocin is administered at a dose of 55 mg/kg of animal weight against the background of a high-fat diet. Correction with hypoglycemic agents in the 3rd group had a positive effect, but it was not able to completely normalize the level of glycemia, so the need arose for the use of additional agents. The use of aflibercept and a nitric oxide donor in the 4th group had a more pronounced positive effect compared to the 3rd group, but the result did not reach the control indicators. Combined administration of bromfenac and aflibercept in the 5th group showed itself to be less effective in the study of the blood glucose level at all stages in comparison with the data of the 4th group, in which the NO donor was involved in the correction. Administation of aflibercept, L-carnitine and bromfenac to the animals of the 6th group had a more pronounced positive effect in comparison with the group No. 5, but did not reach the values of the 4th group of the experiment. The most effective correction was the combination of metformin, aflibercept, L-arginine and citicoline in rats of the 7th group, which is evidenced by the normalization of the level of the studied indicators on the 30th and 60th days of the experiment, and on the 180th, the most pronounced decrease was recorded hyperglycemia.